Effectiveness of Project-Based Learning and Think-Pair-Share Cooperative Learning Models in Improving Students’ Learning Outcomes Based on Their Learning Interest - Grace Fine Situngkir; Saliman Saliman (Jurnal Inovasi Pendidikan dan Sains, 2025)
This study aims to examine the effectiveness of the Project-Based Learning (PjBL) and Think Pair Share (TPS) models in improving students' learning outcomes in social studies subjects viewed from the level of learning interest. This study used a quantitative approach with a quasi-experimental design of the non-equivalent control group pretest-posttest type. The sample consisted of 60 seventh-grade students of SMP Negeri 3 Banguntapan, divided into two experimental groups. The research instruments included a learning outcome test, a learning interest questionnaire, and an observation sheet. Data analysis was conducted using an independent t-test, gain score test, and simple linear regression with the assistance of SPSS. The results of the study showed that both learning models were effective in improving learning outcomes; however, their effectiveness was affected by students’ level of learning interest. The PjBL model was more effective for students with a high level of learning interest, while the TPS model was more suitable for students with moderate to low learning interest. These findings emphasize the importance of selecting learning models that are adaptive to students’ characteristics to optimize learning achievement